Предмет: Алгебра,
автор: fedotova2604
x(x^2+4x+4)=3(x+2) htibnt gj;fkeqcnf
Ответы
Автор ответа:
0
х(х²+4х+4)=3(х+2)
х³+4х²+4х=3х+6
х³+4х²+4х-3х-6=0
х³+4х²+х-6=0
делители числа -6: 1,2,3,6
1+4+1-6=0, значит х=1 - корень нашего уравнения
(х-1)(х²+5х+6)=0
х²+5х+6=0
х₁+х₂=-5
х₁*х₂=6
х₁=-2
х₂=-3
ОТВЕТ: х₁=1
х₂=-2
х₃=-3
х³+4х²+4х=3х+6
х³+4х²+4х-3х-6=0
х³+4х²+х-6=0
делители числа -6: 1,2,3,6
1+4+1-6=0, значит х=1 - корень нашего уравнения
(х-1)(х²+5х+6)=0
х²+5х+6=0
х₁+х₂=-5
х₁*х₂=6
х₁=-2
х₂=-3
ОТВЕТ: х₁=1
х₂=-2
х₃=-3
Похожие вопросы
Предмет: Английский язык,
автор: darkness28911
Предмет: Физика,
автор: romull20002020
Предмет: Астрономия,
автор: ekredina76
Предмет: Информатика,
автор: Schooooooool
Предмет: Литература,
автор: Na26rus2000214